Ecopreneurship in Growing Environmentally Friendly Businesses at the Tannery Industry Center of Star Fruit Village, Besuki District, Bondowoso Regency - Indria Dwi Hapsari; Stivaniyanti Atmanegara; Ismatul Hasanah; Khusnul Mawazin; Tri Bastian Subagio (Jurnal Scientia, 2024)
The Tannery Industry Center of Belimbing Village, located close to Situbondo City and adjacent to residential areas, has a significant impact on the lives of the surrounding community. According to locals, the tannery industry in their region is considered a boon for being the main source of livelihood. The majority of the workforce in the area works as employees in this industrial center. Second, residents also complain of significant pollution impacts on the quality of their living environment, such as air pollution levels that are very disturbing and result in respiratory system disorders. In addition, river 9water pollution has also become a serious issue as a result of ineffective waste management by the tannery industry. This study applies a qualitative research approach, where data are obtained through in-depth interview methods, observation, FGD, literature review, and secondary data analysis. The results show a unique situation in Belimbing Village, where residents depend on industry as a source of livelihood, but at the same time cause negative impacts on air and water quality that reduce their living environment. A number of studies focused on business growth without paying attention to environmental aspects. However, this study explores how an entrepreneur seeks to expand his business by taking into account environmental factors as a key element in managing a business, known as ecopreneurship. Expectations for sustainable business growth are in line with efforts to preserve environmental quality. The majority of business actors in Belimbing Village have not fully adopted the concept of ecopreneurship in their business operations because effective waste management requires significant financial investment. Nevertheless, the continuous increase in sales in the leather industry center of Belimbing Village shows a sustainable business growth.